Bioefficay of Chrysanthemum cinerariifolium and Allium sativum Oil Extracts against Sitophilus zeamais - Lutta, S.; Kituyi, L.; Barasa, S.; Macharia, D. M. (Africa Environmental Review Journal, 2020)
Post harvest grain loss due to insect pests remains a major challenge to farmers globally. The application of synthetic chemicals in pest control has been limited by toxicity, evolution of insect resistance and environmental degradation. This study was done to evaluate the ability of garlic oil extract to synergize pyrethrin against Sitophilus zeamais a significant cereals pest. The phytochemical analysis on pyrethrin with garlic oil confirmed the presences of secondary metabolites that possess insecticidal activities. The experimental design used for bioassay was completely randomized design and tests were done in triplicates. The parameters applied to evaluate efficacy were mortality rates, treatment concentrations and insect’s exposure time. The treatment solutions used for bioassay were varying concentration mixtures of pyrethrin with garlic oil prepared in a ratio of 1:10. The mortality rates were evaluated after 24, 48 and 72 hours. The result showed piperonyl butoxide as the most effective pyrethrin synergist with mean mortality of 90%. The nonsynergized pyrethrum containing 20 mg/ml pyrethrin had less mortality (-%) compared to treatments with lower concentration of pyrethrin that were mixed with garlic oil. The findings revealed that garlic oil can enhance the potency of pyrethrin against Sitophilus zeamias.